Aging-Related Ovarian Failure and Infertility: Melatonin to the Rescue - Russel J. Reiter; Ramaswamy Sharma; Alejandro Romero; Walter Manucha; Dun-Xian Tan; Debora Aparecida Pires de Campos Zuccari; Luiz Gustavo de Almeida Chuffa (MDPI AG, 2023)
Aging has a major detrimental effect on the optimal function of the ovary with changes in this organ preceding the age-related deterioration in other tissues, with the middle-aged shutdown leading to infertility. Reduced fertility and consequent inability to conceive by women in present-day societies who choose to have children later in life leads to increased frustration. Melatonin is known to have anti-aging properties related to its antioxidant and anti-inflammatory actions. Its higher follicular fluid levels relative to blood concentrations and its likely synthesis in the oocyte, granulosa, and luteal cells suggest that it is optimally positioned to interfere with age-associated deterioration of the ovary. Additionally, the end of the female reproductive span coincides with a significant reduction in endogenous melatonin levels. Thus, the aims are to review the literature indicating melatonin production in mitochondria of oocytes, granulosa cells, and luteal cells, identify the multiple processes underlying changes in the ovary, especially late in the cessation of the reproductive life span, summarize the physiological and molecular actions of melatonin in the maintenance of normal ovaries and in the aging ovaries, and integrate the acquired information into an explanation for considering melatonin in the treatment of age-related infertility. Use of supplemental melatonin may help preserve fertility later in life and alleviate frustration in women delaying childbearing age, reduce the necessity of in vitro fertilization-embryo transfer (IVF-ET) procedures, and help solve the progressively increasing problem of non-aging-related infertility in women throughout their reproductive life span. While additional research is needed to fully understand the effects of melatonin supplementation on potentially enhancing fertility, studies published to date suggest it may be a promising option for those struggling with infertility.